2004
DOI: 10.1002/j.2161-1912.2004.tb00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Validation of the Outcome Questionnaire—45: An Assessment of Asian and Pacific Islander College Students

Abstract: This study tested the appropriateness of Outcome Questionnaire45 norms for Asian and Pacific Islander students. Both groups scored higher, based on participants' self-reported general functioning, than the norms and more frequently met criteria for clinical classification, a possible indication of greater distress. The authors discuss findings and therapeutic applications.Este estudio probo la conveniencia de Resultado del Cuestionario-45 normas para 10s estudiantes Asiaticos y lsletio Pacifico. Los dos grupos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Campus studies are important because suicide accounts for a larger proportion of the deaths of 15-24-(and especially 20-24-) year-old Chinese and Japanese Americans than for European Americans. Recent evidence indicates that Asian American university students are more likely than European American students to have psychological concerns that could benefit from treatment (Gregersen, Nebeker, Seely, & Lambert, 2004). Perhaps more importantly, Kisch, Leino, and Silverman (2005) recently found that Asian American students were more likely to attempt suicide than European Americans.…”
mentioning
confidence: 98%
“…Campus studies are important because suicide accounts for a larger proportion of the deaths of 15-24-(and especially 20-24-) year-old Chinese and Japanese Americans than for European Americans. Recent evidence indicates that Asian American university students are more likely than European American students to have psychological concerns that could benefit from treatment (Gregersen, Nebeker, Seely, & Lambert, 2004). Perhaps more importantly, Kisch, Leino, and Silverman (2005) recently found that Asian American students were more likely to attempt suicide than European Americans.…”
mentioning
confidence: 98%
“…However, because 90% of the norm group was Caucasian, some critics (Gregersen, Nebeker, Seely, & Lambert, ; Hanson, Merker, & Pfeiffer, ) have argued that this instrument is not culturally reliable. This instrument measures three separate subscale scores: Symptom Distress, Interpersonal Relationships, and Social Role.…”
Section: Methodsmentioning
confidence: 99%
“…However, the Total score has demonstrated sensitivity to change across a number of studies (Lambert, Burlingame, et al., ; Vermeersch, Lambert, & Burlingame, ; Vermeersch, et al., ). The OQ‐45 has been investigated with various ethnic groups, including African Americans (Nebeker, Lambert, & Huefner, ) and Asian and Pacific Islanders (Gregersen, Nebeker, Seely, & Lambert, ). Gregersen et al () found that although African Americans and Caucasians had comparable scores on the OQ‐45, Asian and Pacific Islanders had higher mean scores than these groups.…”
Section: Criteria and Measuresmentioning
confidence: 99%
“…The OQ-45 has been investigated with various ethnic groups, including African Americans (Nebeker, Lambert, & Huefner, 1995) and Asian and Pacific Islanders (Gregersen, Nebeker, Seely, & Lambert, 2004). Gregersen et al (2004) found that although African Americans and Caucasians had comparable scores on the OQ-45, Asian and Pacific Islanders had higher mean scores than these groups. However, predictive bias was not investigated in either study, so these findings do not necessarily reflect cultural test bias.…”
Section: Evaluating Outcome Measures 817mentioning
confidence: 99%